1983
DOI: 10.1111/j.1536-7150.1983.tb01730.x
|View full text |Cite
|
Sign up to set email alerts
|

The Pursuance of Better Quality of life: In the Long Run, Better Quality of Social Life Is the Most Important Factor in Migration

Abstract: Abstract. A model is developed to explore the relationships between interregional migration and regional variations of quality of life. The model incorporates the impact of the interregional variations of the various aspects of quality of life including economic, political, environmental, social, health and education. The long‐run and short‐run migration data for 65 major U.S. standard metropolitan statistical areas are used to test the model. The results suggest that unlike the conventional conclusions, econ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
2

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 11 publications
2
18
0
2
Order By: Relevance
“…The psychological dimension of life was not taken into account. Other scholars incorporated multiple indicators, such as social welfare, political affairs, education, and medical services to better portray life quality as a whole (Hsieh and Liu 1983). Through economic growth and improvement in social services, rural development efforts have attempted to provide a better quality of life as well as to reduce out-migration.…”
Section: Objective Dimensionmentioning
confidence: 98%
See 1 more Smart Citation
“…The psychological dimension of life was not taken into account. Other scholars incorporated multiple indicators, such as social welfare, political affairs, education, and medical services to better portray life quality as a whole (Hsieh and Liu 1983). Through economic growth and improvement in social services, rural development efforts have attempted to provide a better quality of life as well as to reduce out-migration.…”
Section: Objective Dimensionmentioning
confidence: 98%
“…and to portray the achievement or failure in certain domains of quality of life for a place (Diener and Suh 1997;Hsieh and Liu 1983). Studies that concentrate on the subjective dimension argue that an individual's cognitive perception or satisfaction with a place deserve equivalent attention because such a perception reveals the subjective evaluation of the life experience (Campbell et al 1976;Veenhoven 1996).…”
mentioning
confidence: 98%
“…These changes, it is argued, enhance the role of personal preferences in migration decision-making processes (Zelinsky, 1971). Given research suggesting that individuals often express preferences for residential environments free of environmental hazards (e.g., Blackwood & Carpenter, 1978;Hsieh & Liu, 1983;McAuley & Nutty, 1982), it might be suggested that modernization increases households' ability to act freely upon these preferences for less risky residential environments.…”
Section: Hazardsmentioning
confidence: 99%
“…In addition, levels of air pollution and healthy environments are often noted as desirable residential attributes (e.g., Blackwood & Carpenter, 1978;McAuley & Nutty, 1982). Further, Hsieh and Liu (1983) argue that in the short-run, "pursuance of better environmental quality is the dominant factor in explaining interregional migration" (emphasis in original, p. 431). The rural turnaround of the 1970 s in the U.S. suggested that environmental amenities such as mountains, lakes and "other areas of natural beauty" represent contextual characteristics of importance within rural destinations as well (e.g., DeJong & Sell, 1977:177).…”
Section: Hazardsmentioning
confidence: 99%
“…Estudiar la calidad de vida es conocer las condiciones generales en que vive la comunidad, ya que una mejor calidad de vida no sólo son mayores ingresos (Hsieh y Liu, 1983). Es un proceso de mejora para estar bien socialmente, manifestándolo como el resultado de una combinación de políticas públicas e inversiones en educación, salud y desarrollo de infraestructura, entre otros (Rooy, 1978).…”
Section: Sobre La Calidad De Vida: Conceptos Y Modelounclassified